2022
DOI: 10.1111/nyas.14916
|View full text |Cite
|
Sign up to set email alerts
|

The impact of obesity and adipokines on breast and gynecologic malignancies

Abstract: The link between obesity and multiple disease comorbidities is well established. In 2003, Calle and colleagues presented the relationship between obesity and several cancer types, including breast, ovarian, and endometrial malignancies. Nearly, 20% of cancer‐related deaths in females can be accounted for by obesity. Identifying obesity as a risk factor for cancer led to a focus on the role of fat‐secreted cytokines, known as adipokines, on carcinogenesis and tumor progression. Early studies indicated that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 170 publications
0
1
0
3
Order By: Relevance
“…Of note, this condition might play a role also in the pathogenesis of endometrial cancer. Several preclinical studies proposed multiple theories to explain the association between obesity and the pathogenesis of Prostate cancer (Tewari, Vargas, & Reizes, 2022). Epidemiological studies conducted by CDC reported that obesity is on elevation in the US, as the percentage is increased from 30.5% to 41.9% in the last decades (Tzenios, Tazanios, & Chahine, 2022a).…”
Section: Epidemiology Of Obesity and Endometrial Cancermentioning
confidence: 99%
“…Of note, this condition might play a role also in the pathogenesis of endometrial cancer. Several preclinical studies proposed multiple theories to explain the association between obesity and the pathogenesis of Prostate cancer (Tewari, Vargas, & Reizes, 2022). Epidemiological studies conducted by CDC reported that obesity is on elevation in the US, as the percentage is increased from 30.5% to 41.9% in the last decades (Tzenios, Tazanios, & Chahine, 2022a).…”
Section: Epidemiology Of Obesity and Endometrial Cancermentioning
confidence: 99%
“…A obesidade modifica o status secretor do tecido adiposo, mudando sua homeostase de antiinflamatória para pró-inflamatória, por meio da regulação de adipocinas secretadas (Garcia et al, 2021). As adipocinas também demonstraram promover vias tumorigênicas, incluindo aumento da proliferação de células tumorais e aumento da migração celular (Tewari, 2022).…”
Section: Adipocinas E Câncer De Mamaunclassified
“…As duas adipocinas mais importantes associadas ao desenvolvimento do câncer de mama relacionado à obesidade são a leptina e a adiponectina. A leptina é considerada tanto hormônio quanto adipocina e é produzida e secretada na circulação principalmente pelo tecido adiposo (Tewari, 2022). Os níveis circulantes de leptina comunicam o estado de armazenamento de energia para o cérebro.…”
Section: Adipocinas E Câncer De Mamaunclassified

Estudos Multidisciplinares Sobre Saúde Da Criança E Do Adolescente

RIBEIRO DE SOUSA,
MARQUES DAS CHAGAS,
EDUARDO DA SILVA BARBOSA
et al. 2023
“…Un tema importante relacionado con la obesidad es el cáncer. Se conocen varios mecanismos que han logrado relacionar la obesidad con el cáncer, unos ejemplos son la resistencia a la insulina, la inflamación crónica de bajo grado, estrés oxidativo y las alteraciones que se pueden presentar en el ambiente tumoral; así como la señalización de adipocinas [2], [3]. Se realizó una búsqueda bibliográfica en las bases de datos científicas World Wide Science, Springer Link, PubMed y Google Scholar utilizando palabras clave como: citocinas inflamatorias, obesidad, cáncer e inflamación.…”
Section: Introductionunclassified